Turbine Output Power Settings Analysis on the Performance of Steam Power Plants - Murtalim,; Rahdiana, Nana (International Journal of Psychosocial Rehabilitation, 2020)
Performance of a power plant to be more effective and efficient, the turbine output power regulation must be able to be operated with normal pressure control or sliding pressure control operating methods. This research was obtained by conducting two analytical calculations, namely thermodynamic analysis and direct method analysis. Process parameters needed are feed water flow, coal flow, steam flow, steam temperature, inlet pressure, HHV and SFC. The study was also accompanied by a regression analysis test to determine the significance level of the effect of parameters on the heat rate and also the thermal efficiency that was achieved.